Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Chapter1 Groups Latest Version

Download as pdf or txt
Download as pdf or txt
You are on page 1of 15

GROUP THEORY

MATH 3300

Lebanese University

Faculty of Sciences - Section V

Department of Mathematics

Dr M. ABBASS & Dr S. GHANDOUR

2019-2020
Dr M. ABBASS & Dr S. GHANDOUR

2
Contents

1 Group 5
1.1 Definitions, examples . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 5
1.2 Subgroup - Index - Lagrange’s theorem . . . . . . . . . . . . . . . . . . . . . . . . 6
1.3 Normal subgroup - Quotient group . . . . . . . . . . . . . . . . . . . . . . . . . . 9
1.4 Morphisms - Isomorphism theorems . . . . . . . . . . . . . . . . . . . . . . . . . 11
1.5 Exercises . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 15

3
Dr M. ABBASS & Dr S. GHANDOUR CONTENTS

4
Chapter 1

Group

1.1 Definitions, examples


Definitions.

• A group is a set G together with a binary operation ⋆ such that:

G1) ⋆ is associative (a * b) * c =a * (b * c) for all a,b, c in G


G2) ⋆ has a neutral element e
G3) every element of G has a symmetric for ⋆.

• A group G is said to be commutative or abelian if a ⋆ b = b ⋆ a, ∀a, b ∈ G.

The neutral element of the group G is unique. The symmetric of a given element of G is unique.
The binary operation of the goup G is denoted multiplication. The neutral element is denoted
by e or eG and called the identity element of G, the symmetric of an element x is denoted by
x−1 and called the inverse of x.
-1 -1 -1
For all x, y ∈ G, we have x0 = e and (xy)−1 = y −1 x−1 . By induction (x1x2......xm) = (xm) ...... (x2.) (x1)
-1

For all x ∈ G, m ∈ N∗ we have xm = x·x·· · ··x (m times) and x−m = x−1 ·x−1 ·· · ··x−1 (m times).

Sometimes, when the group G is abelian, its operation is denoted by +. In this case 0G denotes
the neutral element of G and −x denotes the symmetric of the element x, it is called the
opposite of x.
If H is a finite subset of a group G then |H| will denote the number of elements of H.

Examples.

• (Z, +), (Q, +), (R, +) and (C, +) are infinite abelian groups.

• For n ≥ 2 and K = Q, R or C, the set (Mn (K), +) is an infinite abelian group.

• (Q∗ , ·), (R∗ , ·) and (C∗ , ·) are infinite abelian groups.


The set of all n x n invertible matrices with entries in K
• For n ≥ 2 and K = Q, R or C, the set (GLn (K), .) is a non-abelian infinite group.

• For n ∈ N∗ , the set (Z/nZ, +) is a finite abelian group of order n.

5
Dr M. ABBASS & Dr S. GHANDOUR 1.2. SUBGROUP - INDEX - LAGRANGE’S THEOREM

1.2 Subgroup - Index - Lagrange’s theorem


which is a group
Proposition 1.2.1. Let H be a non-empty part of G. The following conditions are equivalent:

a) For all x, y ∈ H we have x−1 ∈ H and x · y ∈ H;

b) For all x, y ∈ H we have x · y −1 ∈ H;

c) (H, ·) is a group.

Proof.

a ⇒ b) Suppose that x−1 ∈ H and x · y ∈ H for all x, y ∈ H. Let x, y ∈ H then x, y −1 ∈ H ⇒


x · y −1 ∈ H.

b ⇒ c) Suppose that for all x, y ∈ H we have x · y −1 ∈ H. Since H ̸= ∅, H contains an element


h so h · h−1 ∈ H ⇒ eG ∈ H. For all x ∈ H we get eG , x ∈ H ⇒ eG .x−1 ∈ H ⇒ x−1 ∈ H.
For all x, y ∈ H we get x, y −1 ∈ H ⇒ x · (y −1 )−1 ∈ H ⇒ x · y ∈ H. We deduce that “ · ”
is a binary operation on H, it is associative, eG ∈ H so “ · ” has a neutral element in H
and every x ∈ H has an inverse x−1 ∈ H. Therefore (H, ·) is a group.

c ⇒ a) Suppose that (H, ·) is a group then “ · ” is a binary operation on H so x · y ∈ H, ∀x, y ∈ H.


Moreover every element of H has an iverse in H. By the unicity of the inverse, we get
x−1 ∈ H, ∀x ∈ H.

Definition. A non-empty part H of G is said to be a subgroup of G if and only if H satisfies


one of the previous properties.

If H is a subgroup of G then the neutral element of G belongs to H.

Examples.

1. For each group G, G and the singleton {e} are two subgroups of G.

2. ({0}, +) is a subgroup of (Z, +), (Z, +) a subgroup of (Q, +),


(Q, +) a subgroup of (R, +), (R, +) a subgroup of (C, +)
and ({1}, ·) is a subgroup of ({−1, 1}, ·), ({−1, 1}, ·) is a subgroup of (Q∗ , ·),
(Q∗ , ·) a subgroup of (R∗ , ·), (R∗ , ·) a subgroup of (C∗ , ·).
aZ ={....,-2a, -a, 0, a, 2a,....} and bZ ={....,-2b, -b, 0, b, 2b,....}
3. For all n ∈ Z, (nZ, +) is a subgroup of (Z, +). so aZ is contained in bZ implies that a is a multiple of b.

4. For a, b ∈ Z, (aZ, +) is a subgroup of (bZ, +) if and only if b divides a.

5. ({1, i, −1, −i}, ·) is a subgroup of (C∗ , ·).

Proposition 1.2.2. If H and K are two subgroups of a group G such that K ⊆ H then K is
a subgroup of H.

Proof. Let H and K be two subgroups of a group G such that K ⊆ H. Then H and K,
equipped with the binary operations induced from G, are two groups. As K ⊆ H, K is a group
for the binary operation induced from H so K is a subgroup of H.

Proposition 1.2.3. The intersection of a non-empty family of subgroups of a group G is a


subgroup of G.

6
Dr M. ABBASS & Dr S. GHANDOUR 1.2. SUBGROUP - INDEX - LAGRANGE’S THEOREM
\
Proof. Let (Hi )i∈I be a non-empty family of subgroups of a group (G, ·) and set H = Hi .
i∈I
We have eG ∈ Hi , ∀i ∈ I ⇒ eG ∈ H ⇒ H ̸= ∅. Let x, y ∈ H then x, y ∈ Hi , ∀i ∈ I ⇒ x · y −1 ∈
Hi , ∀i ∈ I ⇒ x · y −1 ∈ H and H is a subgroup of G.

Proposition 1.2.4. Let H and K be two subgroups of a group G. Then H ∪ K is a subgroup


of G if and only if H ⊆ K or K ⊆ H.

Proof. Let H and K be two subgroups of a group (G, ·). If H ⊆ K or K ⊆ H then H ∪ K = K


or H ∪ K = H, it is a subgroup of G. Suppose now that H ∪ K is a subgroup of G and that
H * K, K * H. Then there exists h ∈ H and k ∈ K such that h ∈ / K and k ∈/ H. We have
h, k ∈ H ∪ K which is a subgroup of G so h.k −1 ∈ H ∪ K ⇒ h.k −1 ∈ H or h.k −1 ∈ K ⇒ k ∈
H or h ∈ K, contradiction. Therefore H ⊆ K or K ⊆ H.

Definition. Let G be a group and X a non-empty part of G. We define the subgroup of G


generated by X, denoted by sg (X), as the smallest subgroup of G containing X.
Proposition 1.2.5. sg (X) is the intersection of all subgroups of G containing X.

Proof. Let T be the intersection of all subgroups of G containing X. As sg (X) is a subgroup


of G containing X, we have T ⊆ sg (X). On the other hand T is a subgroup of G and X ⊆ T ,
so sg (X) ⊆ T . Therefore sg (X) = T . where X is a subset of the group G

Proposition 1.2.6. Set X −1 = {x−1 , x ∈ X}. Then sg (X) is the set of all finite products of
elements of X ∪ X −1 .

Proof. Set T = x1 · x2 · · · · · xm , m ∈ N, xi ∈ X ∪ X −1 . Recall that X ⊆ sg (X) which is a
subgroup of G so X −1 ⊆ sg (X) and all finite products of elements of X ∪ X −1 belong to sg (X),
so T ⊆ sg (X). On the other hand T is a subgroup of G:


 ∅ ̸= X ⊆ T ⇒ T ̸= ∅ and X ⊆ G ⇒ X −1 ⊆ G ⇒ X ∪ X −1 ⊆ G ⇒ T ⊆ G


 Let x ∈ T then x = x1 · · · · · xm , xi ∈ X ∪ X −1
−1 −1
so x−1 = x−1m · · · · · x1 , xi ∈ X ∪ X
−1 ⇒ x−1 ∈ T


 Let x, y ∈ T then x = x1 · · · · · xm , y = y1 · · · · · yn , xi , yj ∈ X ∪ X −1


so x · y = x1 · · · · · xm · y1 · · · · · yn , xi , yj ∈ X ∪ X −1 ⇒ x · y ∈ T

So T is a subgroup of G and X ⊆ T , so sg (X) ⊆ T . Therefore sg (X) = T .


Quotient right coset
Let (G, ·) be a group and H a subgroup of G. For x ∈ G, we set H · x = {h · x, h ∈ H} and
Space
x · H = {x · h, h ∈ H}. We define in G two binary relations R and S by:
• x R y ⇐⇒ x · y −1 ∈ H ⇐⇒ H · x = H · y H x y-1=H y y-1 if and only if H x y-1=H if and only if x.y-1 is in H

• x S y ⇐⇒ x−1 · y ∈ H ⇐⇒ x · H = y · H. x-1 x H=x-1 y H if and only if H =x-1 yH if and only if x-1 y is in H


Note that for x ∈ G we have x · H = H ⇐⇒ x ∈ H ⇐⇒ H · x = H and for x, y ∈ G we have
x R y ⇐⇒ x−1 S y −1 . x R y if and only if x.y-1 is in H if and only if ( x-1)-1 y-1 is in H if and only if x-1 S y-1
Proposition 1.2.7. R and S are two equivalence relations on G.

Proof.
• For all x ∈ G we have x · x−1 = e ∈ H ⇒ x R x and R is reflexive.
−1
• Let x, y ∈ G such that x R y then x · y −1 ∈ H ⇒ y · x−1 = x · y −1 ∈ H ⇒ y R x and
R is symmetric.

7
Dr M. ABBASS & Dr S. GHANDOUR 1.2. SUBGROUP - INDEX - LAGRANGE’S THEOREM

• Let x, y,z ∈ G such −1 −1 −1


−1 −1
 that x R y and y R z then x · y ∈ H and y · z ∈ H ⇒ x · z =
x·y · y·z ∈ H ⇒ x R z and R is transitive.

Therefore R is an equivalence relation on G. Similarly we show that S is an equivalence


relation on G.

Proposition 1.2.8. The class of a element x ∈ G modulo R is H · x and the set of equivalence
G
classes modulo R is = {H · x, x ∈ G}. The class of a element x ∈ G modulo S is x · H
R
G
and the set of equivalence classes modulo S is = {x · H, x ∈ G}.
S
Proof. For x, y ∈ G we have

x R y ⇐⇒ x·y −1 ∈ H ⇐⇒ y·x−1 ∈ H ⇐⇒ y ∈ H·x and x S y ⇐⇒ x−1 ·y ∈ H ⇐⇒ y ∈ x·H.

Proposition 1.2.9. For all x ∈ G we have Card (x · H) = |H| = Card (H · x).

Proof. The mappings ρx : H → H · x and γx : H → x · H defined respectively by ρx (h) = h · x


and γx (x) = x · h are bijective.
   
G G
Proposition 1.2.10. Card = Card .
R S
G G G
Proof. Set f : → such that f (H ·x) = x−1 ·H. Let C1 , C2 ∈ , there exists x1 , x2 ∈ G such
R S R
that C1 = H ·x1 and C2 = H ·x2 . We have C1 = C2 ⇐⇒ H ·x1 = H ·x2 ⇐⇒ x1 R x2 ⇐⇒ x1 ·
x−1
2 ∈ H ⇐⇒ (x1 ) ·x2 ∈ H ⇐⇒ x−1
−1 −1 −1
1 S x2
−1
⇐⇒ x−1 −1
1 ·H = x2 ·H ⇐⇒ f (C1 ) = f (C2 ).
G
So f is a well defined mapping and f is injective. On the other hand every element in has
S
−1
 x · H = 
the form f (H· x ) so f is surjective. We deduce that f is bijective. Therefore
G G
Card = Card .
R S
   
G G G G
Definition. If , or , is finite then Card = Card is called the index of H in
R S R S
G, and it is denoted by |G : H|.

Theorem 1.2.11. Lagrange’s theorem:


If G is a finite group and H is a subgroup of G then

|G| = |G : H| · |H|.

Proof. Let m = |G : H| then there exists x1 , . . . , xm ∈ G such that L(H) = {x1 · H, . . . , xm · H}.
The left equivalence classes modulo H form a partition of G so

|G| = Card(x1 · H) + · · · + Card(xm · H) = m · |H| = |G : H| · |H|.

In particular the orders of the subgroups of a finite group G are divisors of the order of G.

Remark. |G : H| can be finite even if G and H are infinite, for example |Z : 2Z| = 2.

8
Dr M. ABBASS & Dr S. GHANDOUR 1.3. NORMAL SUBGROUP - QUOTIENT GROUP

Proposition 1.2.12. If H and K are two subgroups of a finite group G then

|H| · |K|
Card(H · K) = .
|H ∩ K|

Proof. Set L = H ∩ K and m = |H : L|. There exists x1 , . . . , xm ∈ H such that H =


(x1 · L) ∪ · · · ∪ (xm · L) and (xi · L) ∩ (xj · L) = ∅ iff i ̸= j. We have that x1 · K, . . . , xm · K form
a partition of H · K:

H · K = ((x1 · L) ∪ · · · ∪ (xm · L)) · K ⊆ (x1 · K) ∪ · · · ∪ (xm · K) ⊆ H · K

therefore H · K = (x1 · K) ∪ · · · ∪ (xm · K). Moreover if (xi · K) ∩ (xj · K) ̸= ∅ then there exists
a, b ∈ K such that xi · a = xj · b ⇒ x−1i · xj = a · b
−1 ∈ H ∩ K = L ⇒ x−1 · x ∈ L ⇒ x · L =
i j i
xj · L ⇒ i = j. We deduce that x1 · K, . . . , xm · K form a partition of H · K, so

X
m
|H| · |K|
Card(H · K) = Card(xi · K) = m · |K| = |H : L| · |K| = .
|H ∩ K|
i=1

1.3 Normal subgroup - Quotient group


Proposition 1.3.1. For a subgroup H of (G, ·) the following properties are equivalent:

a) The relations R and S are equal.


G G
b) = .
R S
c) For all x ∈ G we have H · x = x · H.

d) For all x ∈ G we have x−1 · H · x = H.

e) For all x ∈ G and h ∈ H, we have x−1 · h · x ∈ H.

Proof.
G G
a ⇒ b) Suppose that R = S then = .
R S
G G G
b ⇒ c) Suppose that = and let x ∈ G then H · x ∈ ⇒ ∃y ∈ G such that H · x = y · H.
R S R
−1
We have x ∈ y · H ⇒ y · x ∈ H ⇒ y S x ⇒ y · H = x · H ⇒ H · x = x · H.
x= y.h for some h in H which means that y--1 . x=h is in H
c ⇒ d) Suppose that for all x ∈ G we have H · x = x · H and let x ∈ G then x−1 · H · x =
x−1 · x · H = H.

d ⇒ e) Suppose that for all x ∈ G we have x−1 · H · x = H and let x ∈ G then, for all h ∈ H, we
get x−1 · h · x ∈ x−1 · H · x = H.
Need to prove xRy if and only if xSy for all x, y in G
e ⇒ a) Suppose that for all x ∈ G, h ∈ H we have x−1 · h · x ∈ H and let x, y ∈ G. Then
x R y ⇐⇒ x · y −1 ∈ H ⇐⇒ x−1 · (x · y −1 ) · x ∈ H ⇐⇒ y −1 · x ∈ H ⇐⇒ x S y.
Therefore the relations R and S are equal.

9
Dr M. ABBASS & Dr S. GHANDOUR 1.3. NORMAL SUBGROUP - QUOTIENT GROUP

Definition. Let G be a group and H a subgroup of G. We say that H is normal in G or


distinguished in G, and we write H E G, iff H satisfies one of the conditions of the previous
proposition.

In an abelian group, each subgroup is normal.

Proposition 1.3.2. The intersection of a non-empty family of normal subgroups in a group G


is a normal subgroup in G.

Proof.
\ Let (Ni )i∈I be a non-empty family of normal subgroups in a group (G, ·) and set N =
Ni . Then N is a subgroup of G. Moreover let x ∈ G and n ∈ N then n ∈ Ni , ∀i ∈ I ⇒
i∈I
x · n · x−1 ∈ Ni , ∀i ∈ I ⇒ x · n · x−1 ∈ N and N is normal in G.

Proposition 1.3.3. If N is a normal subgroup in a group G then, for all subgroup H of G,


N ∩ H is normal in H.

Proof. Let H and N be two subgroups of a group (G, ·) such that N is normal in G. Since
H, N are subgroups of G then H ∩ N is a subgroup of G. Let x ∈ H ∩ N and g ∈ H then
x, g ∈ H ⇒ g · x · g −1 ∈ H and x ∈ N, g ∈ H ⇒ g · x · g −1 ∈ N as N is normal in G. We
deduce that g · x · g −1 ∈ H ∩ N and H ∩ N is a normal subgroup in H.

Proposition 1.3.4. Let (G, ·) be a group and let K, N be two subgroups of G such that N is
normal in G. Then
sg (K ∪ N ) = K · N = N · K.

Proof. We have N · K = {N · k, k ∈ K} = {k · N, k ∈ K} = K · N as N is normal in G.


Moreover eG ∈ N and eG ∈ K so eG = eG · eG ∈ N · K and N · K ̸= ∅. Let x, x′ ∈ N · K, then
∃n, n′ ∈ N and k, k ′ ∈ K such that x = n · k and x′ = n′ · k ′ . We have x · x′−1 = n · k · k ′−1 · n′−1 =
k · k ′−1k.k'· n
-1.′′k'.k
· n-1′−1
.n.k.k'
′′ = k ′ · k −1 · n · k · k ′−1 ∈ N , so x · x′−1 ∈ K · N = N · K. Therefore
-1.n' -1nis
where in K.N (since N is normal)
We prove
K.N is the K · N = N · K is a subgroup of G. If L is a subgroup of G containing K ∪ N then for all
smallest k ∈ K, n ∈ N we have k ∈ L and n ∈ L ⇒ k · n ∈ L ⇒ K · N ⊆ L. We deduce that K · N is the
subgroup
containing K
smallest subgroup of G containing K ∪ N therefore K · N = sg (K ∪ N ).
and N
Proposition 1.3.5. If N and N ′ are two normal subgroups in a group (G, ·) then N · N ′ is
normal in G.

Proof. N and N ′ are two normal subgroups in a group (G, ·) then N · N ′ is a subgroup of G.
Let x ∈ N · N ′ and g ∈ G then x = n · n′ for some n ∈ N, n′ ∈ N ′ ⇒ g · x · g −1 = g · n · n′ · g −1 =
(g · n · g −1 ) · (g · n′ · g −1 ) ∈ N · N ′ and N · N ′ is normal in G.

Proposition 1.3.6. If H is a subgroup of index 2 in a group G then H is normal in G.

G G
Proof. Let H be a subgroup of index 2 in a group (G, ·). Then
= {H, C} and = {H, C ′ },
S R
with G = H ∪ C = H ∪ C ′ and H ∩ C = ∅ = H ∩ C ′ . For g ∈ G we have g ∈ C ⇐⇒ g ∈ /
H ⇐⇒ g ∈ C ′ so C = C ′ . For x ∈ G we have

• x ∈ H ⇒ x · H = H and H · x = H so x · H = H · x.

/ H ⇒ x · H = C and H · x = C ′ so x · H = H · x.
• x∈

Therefore x · H = H · x for all x ∈ G and H is normal in G.

10
Dr M. ABBASS & Dr S. GHANDOUR 1.4. MORPHISMS - ISOMORPHISM THEOREMS

Definition. A non-trivial group G is said to be simple if {e} and G are the only normal
subgroups in G.
In particular, a simple abelian group is a group with only trivial subgroups.

G G
Let H be a normal subgroup in a group (G, ·) then = , we denote this set by G/H and we
R S
call it the quotient of G by H. For all x ∈ G we have H · x = x · H, and we denote this class
by x. Therefore G/H = {x, x ∈ G} where x = H · x = x · H.
We define on G/H the binary operation x · y = x · y. It is easy to verify that · is well defined
on G/H and that

 (x · y) · z = (x · y) · z = (x · y) · z = x · (y · z) · z = x · (y · z) = x · (y · z) , ∀x, y, z ∈ G,
x · e = x · e = x and e · x = e · x = x, ∀x ∈ G,

x · x−1 = x · x−1 = e and x−1 · x = x−1 · x = e, ∀x ∈ G.

Therefore the set G/H equipped with the operation · is a group, it has e = H as neutral element,
and for all x ∈ G we have (x)−1 = x−1 .
Definition. If H is a normal subgroup in a group (G, ·) then the group (G/H, ·) is called the
quotient group of G by H.
Proposition 1.3.7. Every quotient of an abelian group is an abelian group.

Proof. Let (G, ·) be an abelian group and N a subgroup of G then N is normal in G and the
quotient group is G/N = {x, x ∈ G}. For all ∀x, y ∈ G/N we have x · y = x · y = y · x = y · x
so (G/N, ·) is abelian.

Corollary 1.3.8. If G is a finite group and H is a normal subgroup in G then


|G|
|G/H| = .
|H|

1.4 Morphisms - Isomorphism theorems


Definitions. Let (G, ·) and (G′ , ·) be two groups.
• A group homomorphism from G into G′ is a mapping f : G → G′ such that f (x · y) =
f (x) · f (y), ∀x, y ∈ G.

• A group isomorphism from G into G′ is a bijective group homomorphism from G into


G′ . We say that G and G′ are isomorphic and we write G ∼
= G′ .
• An endomorphism of G is a group homomorphism from G into itself.

• An automorphism of G is a group isomorphism from G into itself.


Definitions. Let G and G′ be two groups and f : G → G′ a group homomorphism.
• The kernel of f is defined by
G'
ker(f ) = f −1 ({eG′ }) = {x ∈ G, f (x) = eG′ } ⊆ G. f

• The image of f is defined by

Im(f ) = f (G) = {f (x), x ∈ G} ⊆ G′ .


Im(f)
Ker(f)
11 eG eG'

G
Dr M. ABBASS & Dr S. GHANDOUR 1.4. MORPHISMS - ISOMORPHISM THEOREMS

Examples.

1. f : (Z, +) → (Z/nZ, +) with f (x) = x is a surjective group homomorphism.

2. For all group (G, ·) and a ∈ G, the conjugation by a, ca : G → G with ca (x) = a · x · a−1
is an automorphism of G.

Proposition 1.4.1. Let (G, ·) and (G′ , ·) be two groups and f : G → G′ a group homomorphism.
We have:

i) f (eG ) = eG′ .

ii) For all x ∈ G, f (x−1 ) = f (x)−1 . = f(G)

iii) For all subgroup H of G, f (H) is a subgroup of G′ . In particular Im(f ) is a subgroup of


G′ .

iv) For all normal subgroup N in G, f (N ) is a normal subgroup in Im(f ).

v) For all subgroup H ′ of G′ , the set f −1 (H ′ ) = {x ∈ G such that f (x) ∈ H ′ } is a subgroup


of G containing ker(f ).

vi) For all normal subgroup N ′ in G′ , f −1 (N ′ ) is a normal subgroup in G. In particular


ker(f ) is a normal subgroup in G.

Proof. f(eG) =f(eG) .f(eG) and since f(eG) is in G' so it is invertible and multiplying both sides with f(eG) -1
i) We have f (eG ) = f (eG · eG ) = f (eG ) · f (eG ) so f (eG ) = eG′ .

ii) We have f (x) · f (x−1 ) = f (x · x−1 ) = f (eG ) = eG′ so f (x−1 ) = f (x)−1 .


h.h' -1is in H as it is a subgroup
iii) Let H be a subgroup of G. We have eG′ = f (eG ) ∈ f (H). Moreover if x, y ∈ f (H) then
∃h, h′ ∈ H such that f (h) = x and f (h′ ) = y, so x · y −1 = f (h · h′−1 ) ∈ f (H). Therefore
f (H) is a subgroup of G′ . Since G is a subgroup of G, Im(f ) = f (G) is a subgroup of G′ . f(N) is contained
in Im(f) which is a
iv) Let N be a normal subgroup in G then f (N ) is a subgroup of Im(f ). For y ∈ Im(f ) subgroup of G'

there exists x ∈ G such that y = f (x). We have y · f (N ) · y −1 = f (x) · f (N ) · f (x)−1 =


f (x · N · x−1 ) = f (N ) and f (N ) is normal in Im(f ).

v) Let H ′ be a subgroup of G′ . For x ∈ ker(f ) (in particular for eG ∈ ker(f )), we have
we proved ker(f) is f (x) = eG′ ∈ H ′ so x ∈ f −1 (H ′ ). Moreover if h, h′ ∈ f −1 (H ′ ) then f (h), f (h′ ) ∈ H ′ , so
contained in f--1(H' )
f (h · h′−1 ) = f (h) · f (h′ )−1 ∈ H ′ , so h · h′−1 ∈ f −1 (H ′ ). Therefore f −1 (H ′ ) is a subgroup
of G containing ker(f ). H' is a group
for all y in x.f-1(N').x-1
y =x.f-1(n').x-1 for vi) Let N ′ be a normal subgroup in G′ then f −1 (N ′ ) is a subgroup of G. For x ∈ G we have
some n' in N'. so
x-1yx=.f-1(n') iff
x · f −1 (N ′ ) · x−1 = f −1 (f (x) · N ′ · f (x)−1 ) = f −1 (N ′ ) and f −1 (N ′ ) is normal in G. Since
n'=f(x-1yx) iff {eG′ } is a normal subgroup in G′ , ker(f ) = f −1 ({eG′ }) is a normal subgroup in G. As N ' is normal then
-1
f(x).N '.f(x) =N '
n'=f(x-1)f(y)f(x) iff
f(y)=f(x)n'f(x-1) iff
y in f-1[ f(x).N'.f(x-1) ]
Corollary 1.4.2. Let G, G′ be two groups and f : G → G′ a group homomorphism. Then
ker(f ) is a normal subgroup in G and Im(f ) is a subgroup of G′ .

Proposition 1.4.3. Let G, G′ be two groups and f : G → G′ a group homomorphism. Then

i) f is injective iff ker(f ) = {eG }.

12
Dr M. ABBASS & Dr S. GHANDOUR 1.4. MORPHISMS - ISOMORPHISM THEOREMS

ii) If f is injective then for all subgroup H of G we have f (H) ∼


= H.

Proof. Let (G, ·) and (G′ , ·) be two groups and f : G → G′ a group homomorphism.

i) Suppose that f is injective and let x ∈ ker(f ) then f (x) = eG′ = f (eG ) ⇒ x = eG
so ker(f ) = {eG }. Conversely suppose that ker(f ) = {eG } and let x, x′ ∈ G such that
f (x) = f (x′ ) then f (x · x′−1 ) = eG′ ⇒ x · x′−1 ∈ ker(f ) ⇒ x = x′ and f is injective.
={ eG }
ii) If f is injective and H is a subgroup of G, then the restriction of f on H, f|H : H → G′
is injective with image f (H) so f (H) ∼
= H. f : H -----------> f(H) is a bijective group homomorphism

f is an Proposition 1.4.4. Let G, G′ be two groups and f : G → G′ a group homomorphism. If f is


isomophism bijective then its inverse f −1 : G′ → G is a group homomorphism.
if and only if f is bijective so f-1 is a map
f -1 is an
isomophism Proof. Let (G, ·) and (G′ , ·)be two groups and f : G → G′ a group isomorphism. For x′ , y ′ ∈ G′ ,
∃!x, y ∈ G such that f (x) = x′ and f (y) = y ′ so f −1 (x′ ) = x and f −1 (y ′ ) = y. We have
x′ · y ′ = f (x) · f (y) = f (x · y) ⇒ f −1 (x′ · y ′ ) = x · y = f −1 (x′ ) · f −1 (y ′ ) and f −1 is a group
homomorphism.

Proposition 1.4.5. Let G, G′ and G′′ be three groups and f : G → G′ , g : G′ → G′′ two group
homomorphisms. Then

i) g ◦ f is a group homomorphism from G to G′′ .

ii) If f and g are two group isomorphisms then g ◦ f is a group isomorphism.

Proof. Let (G, ·), (G′ , ·) and (G′′ , ·) be three groups and f : G → G′ , g : G′ → G′′ two group
homomorphisms.

i) For all x, y ∈ G we have (g ◦ f )(x · y) = g(f (x · y)) = g(f (x) · f (y)) = g(f (x)) · g(f (y)) =
(g ◦ f )(x) · (g ◦ f )(y) so g ◦ f is a group homomorphism from G to G′′ .

ii) If moreover f and g are bijective then so is g ◦ f , it is a group isomorphism.

Definition. Let G be a group and Aut (G) the set of automorphisms of G then (Aut (G), ◦) is
a group called the automorphism group of G.

Proposition 1.4.6. Let G, G′ be two groups and f : G → G′ a group homomorphism. Each


subgroup (respectively normal subgroup) of Im(f ) has the form f (H) where H is a subgroup
(respectively a normal subgroup) of G containing ker(f ).

Proposition 1.4.7. Let N be a normal subgroup in a group G. The subgroups (respectively the
normal subgroups) of the quotient group G/N are the quotients H/N of the subgroups (respec-
tively of the normal subgroups) H of G containing N .

Proof. The canonical surjection ΠN : G → G/N is a surjective group homomorphism with kernel
N . So there exists a bijection between the set of subgroups of G containing ker (ΠN ) = N and
the set of subgroups of Im (ΠN ) = G/N .

Proposition 1.4.8. Let N be a normal subgroup in a group G then If H and K are subgroups
of G containing N then H ⊆ K in G iff H
N ⊆ N in G/N .
K

Ker(f)=N
13 G/N
N
G
f
G ---------> Im(f) G'

f
G/ker(f)
Dr M. ABBASS & Dr S. GHANDOUR 1.4. MORPHISMS - ISOMORPHISM THEOREMS

Theorem 1.4.9. First isomorphism theorem:


Let G, G′ be two groups and f : G → G′ a group homomorphism. Then
G/ ker(f ) ∼
= Im(f ).
Proof. Let (G, ·) and (G′ , ·) be two groups and f : G → G′ a group homomorphism. Then ker(f )
is a normal subgroup in G, G/ ker(f ) = {x, x ∈ G} is the quotient group of G by ker(f ). On the
other hand Im(f ) = f (G) is a subgroup of G′ so Im (f ) is a group. Set f : G/ ker(f ) → Im (f )
such that f (x) = f (x), ∀x ∈ G/ ker(f ). For x, y ∈ G/ ker(f ) we have
x = y ⇐⇒ x · y −1 ∈ ker(f ) ⇐⇒ f (x · y −1 ) = eG′ ⇐⇒ f (x) = f (y) ⇐⇒ f (x) = f (y).
So f is well defined and it is injective.
 Each element in Im(f )has the form f (x) = f (x) for
some x ∈ G so Im(f ) ⊆ Im f ⊆ Im(f ) ⇒ Im(f ) = Im f and f is surjective. For all
x, y ∈ G/ ker(f ) we have
f (x · y) = f (x · y) = f (x · y) = f (x) · f (y) = f (x) · f (y)
therefore f is a group homomorphism. We deduce that f : G/ ker (f ) → f (G) is a group
isomorphism and G/ ker(f ) ∼
= Im(f ).
Theorem 1.4.10. Second isomorphism theorem:
Let H and N be two subgroups of a group (G, ·) such that N is normal in G then
p(h.k)= hk.N
=hN.kN H ·N ∼ H
= .
= p(h).p(k) N H ∩N
so that p is a
group Proof. Since N is a normal subgroup in G, H · N is a subgroup of G and N is normal in H · N .
H ·N
homomorph. Let iH : H → H · N be the canonical injection and let ΠN : H · N → be the canonical
N
H ·N
Now define the
surjection. Setmapping
p = ΠN ◦ iH then p : H →
p by: is given by p(h) = h = h · N and p is a group
N
homomorphism. Let h ∈ H then h ∈ ker(p) ⇐⇒ h = eG ⇐⇒ h ∈ N ⇐⇒ h ∈ H ∩ N
H ·N =N
so ker(p) = H ∩ N . For all x ∈ , there exists h ∈ H and n ∈ N such that x = h · n =
N
H ·N
h · n = h · eG = h = p(h) so Im(p) = and p is surjective. Therefore H/ ker(p) ∼= Im(p) ⇒
N
H ∼ H ·N |H| · |N |
= . In particular, if G is finite, then |H · N | = .
H ∩N N |H ∩ N |
Theorem 1.4.11. Third isomorphism theorem:
Let H and N be two normal subgroups in a group G such that N ⊆ H. Then
G/N ∼ G
= .
H/N H
x.N ---------------------> x.H
Proof. Let H and N be two normal subgroups in a group (G, ·) suvh that N ⊆ H. Set G/N =
{x, x ∈ G} where x = x · N and G/H = {b x, x ∈ G} where x b = x · H. Let ϕ : G/N → G/H
such that ϕ (x) = x b for all x ∈ G. Let x, y ∈ G/N then x = y ⇐⇒ x · y −1 ∈ N ⇒ x · y −1 ∈
H ⇐⇒ x b = yb ⇐⇒ ϕ(x) = ϕ(y) so ϕ is a well defined mapping. For all x, y ∈ G/N we have
ϕ(x · y) = ϕ(x · y) = xd ·y = xb · yb = ϕ(x) · ϕ(y) so ϕ is a group homomorphism. Let x ∈ G/N
then x ∈ ker(ϕ) ⇐⇒ ϕ (x) = eG/H ⇐⇒ x b = ecG ⇐⇒ x · H = H ⇐⇒ x ∈ H ⇐⇒ x ∈ H/N
and ker(ϕ) = H/N . Each element in G/H has the form x · H = x b = ϕ (x) for some x ∈ G
(G/N ) ∼
so G/H ⊆ Im ϕ ⊆ G/H ⇒ Im(ϕ) = G/H and ϕ is surjective. Therefore = Im(ϕ) ⇒
ker(ϕ)
G/N ∼ G
= .
H/N H

14
Dr M. ABBASS & Dr S. GHANDOUR 1.5. EXERCISES

1.5 Exercises
Exercise 1.1. Let H be a subgroup of a group G. Show that

i) aHa−1 is a subgroup of G for all a ∈ G.

ii) If H is finite then aHa−1 is finite and |aHa−1 | = |H|.



iii) NG (H) = x ∈ G / xHx−1 = H is a subgroup of G.

iv) H E G ⇐⇒ NG (H) = G.

v) If |H| = n and |K| ̸= n for every subgroup K ̸= H of G then H E G.

Exercise 1.2. Show that if H is a subgroup of index 2 in a group G then H E G.

Exercise 1.3. Let G be a group such that x2 = e for all x ∈ G. Show that G is abelian.

Exercise 1.4. Let H and K be two subgroups of a group G. Show that H ∪ K is a subgroup
of G if and only if H ⊆ K or K ⊆ H.

Exercise 1.5. The center of a group (G, ·), denoted by Z(G), is defined to be the set

Z(G) = {z ∈ G such that z.g = g.z, ∀g ∈ G}.

Show that Z(G) is a normal subgroup in G.

Exercise 1.6. Let f : G → G′ be a group isomorphism. Show that f (Z(G)) = Z(G′ ).

Exercise 1.7. Let G be a simple group and let f : G → H be a group homomorphism. Show
that Im f = {eH } or G ∼
= Im f .

Exercise 1.8. Let G be a group and set S = x2 , x ∈ G and H = sg (S).

i) Show that H E G.

ii) Show that G/H is abelian.

Exercise 1.9. Let G and H be two finite groups and f : G → H a group homomorphism. Let
K be a subgroup of G such that |H| ∧ |K| = 1. Show that K ⊆ ker (f ).

Exercise 1.10. Let (G, ·) be a finite group, H and K two normal subgroups in G.

1. Show that |G : (H.K)| divides |G : H|.

2. Deduce that if |G : H| ∧ |G : K| = 1 then G = H.K.

15

You might also like